Semantic Web service and pervasive information system conceptual adaptation. Issue 4 (7th November 2016) - Fatma, Achour; Jedidi, Anis; Gargouri, Faiez
Abstract : Purpose: One of the open questions is how to ensure the conceptual adaptation in the pervasive system. To answer this question, the authors needed to propose a generic model and a mechanism to describe this system and also need generic and semantic rules to ensure the adaptation. This paper aims to propose a model to describe the pervasive information system. Second, the authors suggest an approach to divide this model so as to describe each category of contextual information separately and ensure the adaptation in the pervasive system. Finally, the authors present examples of semantic rules executed in the pervasive system. Design/methodology/approach: This paper proposes an approach to ensure the conceptual adaptation in the pervasive system. To do it, the authors proposed a model to design the pervasive system and used semantic Web services. They proposed to divide the model to six descriptions related to the pervasive system categories information. Findings: Pervasive information system, conceptual adaptation, semantic Web services and OWL-S are presented in this paper. Originality/value: The originality of this paper is presented in the purpose of the pervasive information system conceptual adaption in the pervasive system. In this, later, semantic Web services were used to ensure the adaptation by the adding of contextual information in the semantic Web service description.